Cardiac Resynchronization Therapy With Wireless Left Ventricular Endocardial Pacing: The SELECT-LV Study - Reddy, Vivek Y; Miller, Marc A; Neuzil, Petr; Søgaard, Peter; Butter, Christian; Seifert, Martin; Delnoy, Peter Paul; van Erven, Lieselot; Schalji, Martin; Boersma, Lucas V A; Riahi, Sam (Journal of the American College of Cardiology, 2017)
BACKGROUND: A total of 30% to 40% of patients with congestive heart failure eligible for cardiac resynchronization therapy (CRT) either do not respond to conventional CRT or remain untreated due to an inability or impediment to coronary sinus (CS) lead implantation. The WiSE-CRT system (EBR Systems, Sunnyvale, California) was developed to address this at-risk patient population by performing biventricular pacing via a wireless left ventricular (LV) endocardial pacing electrode. OBJECTIVES: The SELECT-LV (Safety and Performance of Electrodes implanted in the Left Ventricle) study is a prospective multicenter non-randomized trial assessing the safety and performance of the WiSE-CRT system. METHODS: A total of 35 patients indicated for CRT who had "failed" conventional CRT underwent implantation of an LV endocardial pacing electrode and a subcutaneous pulse generator. System performance, clinical efficacy, and safety events were assessed out to 6 months post-implant. RESULTS: The procedure was successful in 97.1% (n = 34) of attempted implants. The most common indications for endocardial LV pacing were difficult CS anatomy (n =12), failure to respond to conventional CRT (n = 10), and a high CS pacing threshold or phrenic nerve capture (n = 5). The primary performance endpoint, biventricular pacing on the 12-lead electrocardiogram at 1 month, was achieved in 33 of 34 patients. A total of 28 patients (84.8%) had improvement in the clinical composite score at 6 months, and 21 (66%) demonstrated a positive echocardiographic CRT response (≥5% absolute increase in LV ejection fraction). There were no pericardial effusions, but serious procedure/device-related events occurred in 3 patients (8.6%) within 24 h, and 8 patients (22.9%) between 24 h and 1 month. CONCLUSIONS: The SELECT-LV study demonstrates the clinical feasibility for the WiSE-CRT system, and provided clinical benefits to a majority of patients within an otherwise "failed" CRT population. (Safety and Performance of Electrodes Implanted in the Left Ventricle [SELECT-LV]; NCT01905670).
Keywords: Cardiac Resynchronization Therapy Devices; prostředky srdeční resynchronizační terapie; Female; leadless pacemaker; ženské pohlaví; Heart Failure; Cardiac Resynchronization Therapy; lidé; srdeční selhání; Treatment Failure; srdeční resynchronizační terapie; cardiac resynchronization therapy; prospektivní studie; Male; Aged; Prospective Studies; neúspěšná terapie; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans